Review: Pincer ligands—Tunable, versatile and applicable. (15th March 2018) - Lawrence, Mark A.W.; Green, Kerry-Ann; Nelson, Peter N.; Lorraine, Shannen C.
Graphical abstract: Pincer ligands and their metal complexes are ubiquitous in coordination and organometallic chemistry owing to the unusual properties they impart on the metal centers to which they are coordinated. They have wide ranging applications and this review explores various categories of pincer ligands and the metal complexes. Abstract: Pincer ligands continue to generate interest owing to the unusual properties they impart on metal centers and consequently on the complexes they are involved in. These ligands and their metal complexes have aided in the understanding of a number of processes mediated by organometallic and non-organometallic systems. In homogenous catalytic transformations, pincer ligands provide enhanced chemical and thermal stability which serve to minimize the leaching of the metal during the catalytic cycle. These ligands also offer the ability to fine tune the electronic and the steric properties about the metal center, thereby increasing the scope of their applications. This review discusses some of the general synthetic protocols of the main classes of pincer ligands with a focus on some of their more popular applications.